(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Nowadays, economy’s globalization, with its progressive process of opening upmarkets, has turned the business environment in an environment characterized by high competitiveness. Therefore, it is necessary not only to accept the changes, but to anticipate them by flexible and continuous adaptations of structures, systems and business procedures. It is understood that nonstop training reaches the training needs posed by the present global society, as it becomes a strategy to meet the challenges of globalization and to move towards what is known as “new enterprise culture”.The objective is to raise a new business model based on long -term viewpoint,total quality, personal self-assertion, joint participation in decision-making and permanent training, among other things, becoming the model par excellence that competitive organizations face the challenges of globalization with success. For this reason, a study on which are the current training trends has been carried out, identifyingthe training methodologies that are been most used by the companies of theSpanish panorama.